2020
DOI: 10.3389/fphar.2020.532849
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in the Regulation of Asthma: Current Research and Clinical Implications

Abstract: Asthma is a chronic airway inflammatory disorder related to variable expiratory airflow limitation, leading to wheeze, shortness of breath, chest tightness, and cough. Its characteristic features include airway inflammation, airway remodeling and airway hyperresponsiveness. The pathogenesis of asthma remains extremely complicated and the detailed mechanisms are not clarified. Long noncoding RNAs (lncRNAs) have been reported to play a prominent role in asthma and function as modulators of various aspects in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“… 85 The miR‐203a targets the 3′‐untranslated region of E2F transcription factor 3 (E2F3), a positive regulator, that be involved in DNA replication by stimulating the entry of quiescent cells into the G1/S phase of the cell cycle. 86 , 87 Therefore, down regulation of lnc‐PVT1 has positive effect on the treatment of RSV infection.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“… 85 The miR‐203a targets the 3′‐untranslated region of E2F transcription factor 3 (E2F3), a positive regulator, that be involved in DNA replication by stimulating the entry of quiescent cells into the G1/S phase of the cell cycle. 86 , 87 Therefore, down regulation of lnc‐PVT1 has positive effect on the treatment of RSV infection.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…Based on these data, several studies have shown that lncRNAs are involved in a variety of biological and physiological processes and are directly related to various cancers, coronary artery disease, and many other diseases affecting humans [ 6 8 ]. It is reported that LncRNAs also play many regulatory roles in the pathological process of asthma, including helper T cell (Th)1/Th2 imbalance, eosinophil dysfunction, macrophage polarization, airway smooth muscle cell proliferation and glucocorticoid insensitivity [ 9 ]. Technological advances have allowed for a better understanding of the complex pathogenesis of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…This study generates new insights into the pathogenesis of asthma by integrating disease characteristics, pathways, and SNPs information. Three typical disease characteristics were scrupulously determined according to the summary of asthma characteristics in classic retrospective articles ( Papi et al, 2018 ; Zhu et al, 2020b ), i.e., airway inflammation, airway hyperresponsiveness, and airway remodeling, etc. A contemporary catalog of corresponding risk transcriptome including mRNAs, miRNAs, and lncRNAs was manually established.…”
Section: Introductionmentioning
confidence: 99%